The Past Perfect in Corpora and EFL/ESL Materials - Vandenhoek, Tim (Research in Language, 2018)
Corpora provide teachers and materials developers with the ability to ensure that the instructions they use in class and in teaching materials correctly reflect natural use. This paper examines the ways in which grammar reference books and two types of EFL/ESL materials present the past perfect aspect and whether they do so accurately. It will be argued that there are several issues concerning how these books present the grammar point. Many of the books surveyed provide incomplete explanations of when and how the form is used and several contain usage guidelines that are not supported by available corpus data. The paper ends with several recommendations to improve how the form is presented to teachers and learners.